Minimizing Process Water and Energy Consumption in Styrene Production by Ethylbenzene Dehydrogenation - Najib, Muchammad Ilham; Hestiawan, Felicia; Pratiwi, Amelia; Pangayom, Lintang Bagas (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
Styrene is a crucial unsaturated aromatic monomer with a wide range of industrial applications. Styrene production faces several problems where the water supply and energy usage are keep increasing. Process modifications were implemented to minimize process water and to optimize the energy consumption. The modification uses Aspen HYSYS simulation by replacing coolers and heaters with heat exchanger and implementing water recycling system. Aspen HYSYS simulations show these changes reduce water usage by 89.8% and significantly decrease energy consumption up to 54.69%. This modification shows the water and energy usage have been significantly reduced than the basic process. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).